Cyber-physical Systems and Artificial Intelligence: The Role of Cyber Security, Machine Learning, Threats and benefits to Modern Economies and Industries - Naqvi , Syed Gulfraz; Sheraz, Sheriyar; Mehmood, Ikhlas; Yasin, Muzzamil (Pakistan Journal of Humanities and Social Sciences, 2023)
We have seen several applications based on embedded system principles evolve during the last 20 years. However, embedded systems are only useful for standalone, modest-sized applications. The use of artificial intelligence (AI) in cyber-physical systems is now and, in the future, faced with several difficulties. It also looks at how machine learning, the contemporary economy, and business interact with cybersecurity and artificial intelligence. The emphasis of the literature study is on developing a conceptual framework that will enable automation at both the technological and human levels, hence enhancing AI's resilience. Paradigm changes are a reality in contemporary culture. New technologies that provide high-performance computing capabilities that allow the development of intricate artificial intelligence systems are a contributing factor in these shifts. These advancements have made it possible for brand-new cybernetic systems to emerge, in which artificial intelligence models are employed to carry out specific jobs inside the system using continually produced data. On the one hand, cyber systems are being used more and more often in isolated applications. On the other hand, there is still discussion around the simultaneous integration of cyber systems with other cyber systems, the creation of straightforward cognitive structures, and the profound autonomy of interaction with physical systems. Widely open issue that has only been addressed philosophically in select texts.